Penggunaan Sosial Media Whatsapp Sebagai Media Pembelajaran Ekonomi di SMAN 13 Padang - Dendhi Arizal Aulia Putra; Armiati Armiati (Jurnal Salingka Nagari, 2023)
This study aims to (1) analyze the use of social media whatsapp as a medium of economic learning at SMAN 13 Padang and (2) find out the obstacles to using social media whatsapp as a medium of economic learning at SMAN 13 Padang. This research is a qualitative descriptive study. Research informants are Economics teachers and Social Studies students in grades X, XI, and XII at SMAN 13 Padang. Data collection techniques are observation, interviews, and documentation. The technique of checking the validity of the data uses source triangulation. The results showed that (1) the use of Whatsapp as a Social Media for Economic Learning at SMAN 13 Padang is almost the same as face-to-face activities, like preparing the subject matter; students and teachers communicating and discussing; giving assignments, and collecting assignments. (2) The problem with using Whatsapp social media as a medium of economic learning at SMAN 13 Padang is that students lack focus; internet signal disturbances, full cell phone quotas and charges, low student willingness to learn, lack of interaction, difficulty understanding the material provided by the teacher, the living environment does not support the learning process, impaired student eye health, and queued absenteeism.